Estimate of the modulus of continuity of a cauchy-type integral in a domain and on its boundary - Gerus, O. F. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We estimate the modulus of continuity of a Cauchy-type integral in a closed domain and its limit values on the boundary in the case where the boundary of the domain is an arbitrary closed rectifiable Jordan curve.